Workshop based on the free play time methodology in the sectors to develop social interaction skills - Mendoza Núñez, Rossicielo (2016)
The main objective ofthis research was to determine how influential a workshop based on the free play time methodology in the sectors to develop social interaction skills is in three-year-old children. The sample used was of 20 children, both boys and girls. A social interaction skills questionnaire by Inés Monjas Casares was applied to the sample. Then the workshop based on the free play time methodology in the sectors to develop social interaction skills was applied to the children from the experimental group. The data obtained was processed and analyzed using Excel. The results obtained show that the social interaction skills level was low before applying the workshop according to the measurement obtained in the pretest for both groups. Statistically there were not signi:ficant differences in them according to the t hypothesis by Student. Then a workshop of 20 activities based on the free play time methodology in the sectors to develop social interaction skills in the children from the experimental group. Later the results from the post test showed that the workshop had a significant influence in the social interaction development. Finally, after making the result discussion and the predicted hypothesis test, it is concluded that the workshop based on the free play time methodology in the sectors influenced signi:ficantly in the social interaction skills development in three-year-old children from the Pasito a Paso school, 2015.